2014
DOI: 10.1097/nna.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Shift Reports

Abstract: Bedside shift reports are viewed as an opportunity to reduce errors and important to ensure communication between nurses and communication. Models of bedside report incorporating the patient into the triad have been shown to increase patient engagement and enhance caregiver support and education. Nurse shift reports and nurse handovers are 2 of the most critical processes in patient care that can support patient safety and reduce medical errors in the United States. Nurses continue to not recognize the evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…Another potential explanation is that nurses do not trust the information in the EHR. Indeed a prior study suggested that nurses preferentially depend on either bedside information or verbal communication (Collins, Bakken, Vawdrey, Coiera, & Currie, 2011b;Gregory, Tan, Tilrico, Edwardson, & Gamm, 2014). This is also supported by another study that demonstrated nursing students are more likely to report incorrect vital signs that were conveyed to them at the bedside by medical students.…”
Section: Discussionmentioning
confidence: 77%
“…Another potential explanation is that nurses do not trust the information in the EHR. Indeed a prior study suggested that nurses preferentially depend on either bedside information or verbal communication (Collins, Bakken, Vawdrey, Coiera, & Currie, 2011b;Gregory, Tan, Tilrico, Edwardson, & Gamm, 2014). This is also supported by another study that demonstrated nursing students are more likely to report incorrect vital signs that were conveyed to them at the bedside by medical students.…”
Section: Discussionmentioning
confidence: 77%
“…The bedside handover, where the nurse-to-nurse handover is performed at the patient's bedside (Anderson & Mangino, 2006), is an upcoming method in nursing due to the many advantages attributed to it (Gregory, Tan, Tilrico, Edwardson, & Gamm, 2014). Still, the body of knowledge on this topic is limited because of the lack of longitudinal, multicentred studies (Smeulers, Lucas, & Vermeulen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The assumption about the positive effects of bedside handover is grounded in the consequences of performing the nursing handover at the patient's bedside (Gregory et al, 2014). First, due to the patient's presence the information transfer between nurses is improved as irrelevant information is avoided and information given is more accurate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations